Pathways into Self-Employment in the United States and Germany - Patricia A. McManus (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
Using longitudinal data from the Panel Study of Income Dynamics and the German Socio-Economic Panel, this research compares pathways into self-employment among men and women in the United States and Western Germany. Academic and vocational credentials are more important for stabilizing self-employment in the United States than in Germany, where the lack of credentials is a significant deterrent to self-employment entry. Intergenerational transmission of self-employment is more prominent among men than among women in both countries, while spousal transmission of self-employment status is more prominent among women. In both countries, women's self-employment mobility is sensitive to domestic responsibilities.
Keywords: 330; Selbstständige; Geschlecht; Vergleich; USA; Deutschland; Berufsrecht